Immune Cell Landscape Identification Associates Intrarenal Mononuclear Phagocytes With Onset and Remission of Lupus Nephritis in NZB/W Mice - Li, Bin; Tang, Yanlai; Ni, Xuhao; Chen, Wei (Frontiers in Genetics, 2020)
Objective: A challenging issue in the clinical management of lupus nephritis (LN) is the resistance to immunosuppressive therapy. We postulated that perturbed intrarenal immune cell landscape affected LN onset and remission induction, and shedding light on the characteristics of intrarenal immune cell infiltration could cultivate more efficient treatment regimens. Materials and Methods: Genome-wide expression profiles of microarray datasets were downloaded from the Gene Expression Omnibus database. The CIBERSORT algorithm was used to analyze the intrarenal immune cell landscape, followed by Pearson correlation analysis and principal component analysis. The differentially expressed genes were identified and subjected to Gene Ontology (GO) enrichment analyses and protein-protein interaction network establishment, being visualized by Cytoscape and further analyzed by CytoHubba to extract hub genes. Hub genes were also validated in the genomic dataset from kidney biopsy-proven LN patients. Results: In addition to memory B cells, monocytes and M1 macrophages were identified as two predominantly increased intrarenal immune cell types in LN-prone NZB/W mice upon nephritis onset. Most interestingly, apart from memory B cells, monocytes and M1 macrophages proportions in kidney tissue were significantly lower in early-remission mice compared with late-remission mice. Furthermore, GO analysis showed that intrarenal mononuclear phagocytes triggered nephritis onset mainly via the initiation of adaptive immune response and inflammatory reaction, but this functional involvement was mitigated upon remission induction. Hub genes related to LN onset in NZB/W mice were validated in the genomic dataset from kidney biopsy-proven LN patients. Conclusion: LN characterizes aberrant mononuclear phagocytes abundance and signature upon disease onset, of which the reversal is associated with early remission induction in LN-prone NZB/W mice. Mononuclear phagocytes might be an adjunctive histology marker for monitoring disease onset and stratifying LN patients in terms of response to remission induction therapy.